Genomics Study of Mycobacterium tuberculosis Strains from Different Ethnic Populations in Taiwan. (January 2016) - Dou, Horng-Yunn; Chen, Yin-Yuan; Chen, Ying-Tsong; Chang, Jia-Ru; Lin, Chien-Hsing; Wu, Ken-Ming; Lin, Ming-Shian; Su, Ih-Jen; Tsai, Shih-Feng
To better understand the transmission and evolution of Mycobacterium tuberculosis (MTB) in Taiwan, six different MTB isolates (representatives of the Beijing ancient sublineage, Beijing modern sublineage, Haarlem, East-African Indian, T1, and Latin-American Mediterranean (LAM)) were characterized and their genomes were sequenced. Discriminating among large sequence polymorphisms (LSPs) that occur once versus those that occur repeatedly in a genomic region may help to elucidate the biological roles of LSPs and to identify the useful phylogenetic relationships. In contrast to our previous LSP-based phylogeny, the sequencing data allowed us to determine actual genetic distances and to define precisely the phylogenetic relationships between the main lineages of the MTB complex. Comparative genomics analyses revealed more nonsynonymous substitutions than synonymous changes in the coding sequences. Furthermore, MTB isolate M7, a LAM-3 clinical strain isolated from a patient of Taiwanese aboriginal origin, is closely related to F11 (LAM), an epidemic tuberculosis strain isolated in the Western Cape of South Africa. The PE/PPE protein family showed a higher dn/ds ratio compared to that for all protein-coding genes. Finally, we found Haarlem-3 and LAM-3 isolates to be circulating in the aboriginal community in Taiwan, suggesting that they may have originated with post-Columbus Europeans. Taken together, our results revealed an interesting association with historical migrations of different ethnic populations, thus providing a good model to explore the global evolution and spread of MTB.